PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS 9A SMPN 5 TELUK KUANTAN - Syafrida Haryati (Riau Education Journal, 2021)
Classroom Action Research was carried out to improve students' learning activities and learning outcomes using STAD cooperative learning in Class 9A SMPN 5 Teluk Kuantan. Cooperative learning model type Student Team-Achievment Divisions (STAD) is a cooperative learning method, where students work in their teams to ensure that all team members have mastered the lesson through quizzes.Â  To obtain research data, an observation sheet was used to observe student activities filled in by the observer and a learning outcome test given at the end of the cycle. Data on student learning activities were analyzed by determining the number and percentage of students involved in each meeting. The increase in learning outcomes is seen from the number of students who complete at the end of the cycle. The results showed that learning activities and student learning outcomes experienced an increase where in the initial data from 20 students only 7 people reached the KKM after the action in the first cycle was the average student score was 71, increased in the second cycle to 86.5 so it increased as many as 15.5, but there are still some students who have not reached the KKM score. The results of the study show that STAD cooperative learning can improve mathematics learning outcomes for Grade 9A students of SMPN 5 Teluk Kuantan